THE SILENT PANDEMIC: A COMPREHENSIVE ANALYSIS OF THE IMPACT OF AIR POLLUTION ON HUMAN HEALTH - Asatullyev Rustam Baxtiyorovich; Sobirova Maftunaxon Azamatjon qizi (TADQIQOTLAR, 2026)
Abstract: Air pollution is the world’s largest single environmental health risk, contributing to approximately 7 million premature deaths annually. This article provides a systematic review of the impact of air pollution on human health, focusing on particulate matter (PM2.5 and PM10), nitrogen dioxide (NO2), ozone (O3), and other toxic gases. The analysis covers the pathophysiology of exposure, including oxidative stress and systemic inflammation, and details the clinical consequences for the respiratory, cardiovascular, neurological, metabolic, and reproductive systems. Special attention is given to vulnerable populations, including children, the elderly, pregnant women, and socioeconomically disadvantaged communities. The article also discusses environmental justice issues, recent epidemiological findings, and evidence- based mitigation strategies. The review concludes that while air pollution remains a global health emergency, targeted policy interventions, technological innovation, and public health measures can substantially reduce the burden of disease.